EFEKTIFITAS KOMUNIKASI PERSUASIF PENYULUH AGAMA HINDU NON PNS DALAM MEMBINA KELUARGA DHARMIKA DI KOTA MATARAM - NI NYOMAN HARNIKA (Universitas Mahasaraswati K. Mataram, 2021)
Communications and a man holding a role which is very important in the life of a day man. Due to the communication of man can perform interactions with others. An extension of Hinduism that has the duty to spread the teachings of Hinduism to the people of the Hindu with the purpose of the people Hindu to implement the teachings of religion with good. Communications are carried by extension Hinduism Non PNS in fostering people of Hindu is communication persuasive, communication that aims to influence the people of Hindu especially families darmika to be able to run the teaching of religion in accordance literary religion. The purpose of this research is to describe communication persuasive non-civil servant Hindu religious instructor in fostering a darmika family. The theory that is used in research this is the theory of the theory of change of attitude (attitude change theory). The method that is used in research this is a study of qualitative descriptive with outlines in communication persuasive extension of Hinduism Non PNS in fostering. The collection of data using purposive side. The result of this research is a persuasive communication process for non-civil servant Hindu religious instructors in fostering darmika families. This is done by taking into account the credibility of the communicator, persuasion in verbal and non-verbal contexts, message selection and media use. The effectiveness of communication persuasive in research this is the occurrence of a change in family darmika as srada were done by family darmika is getting stronger, things are seen from the family darmika implement the Tri Hita Karana in life.